MODEL BISNIS KANVAS DOC AYAM KAMPUNG PT PQR : BUSINESS MODEL CANVAS OF NATIVE CHICKEN DOC PT PQR - Dewi, Aomi Hazelia; Sukardi,; Taqi, Fahim M. (Jurnal Aplikasi Bisnis dan Manajemen, 2020)
The poverty reduction program by the Indonesian government in 2018-2019 had appointed PT. PQR as the distributor of native chicken DOC. This study aimed to analyze the current PT PQR business model and improve the business model. The study used the Business Model Canvas. The findings were the followings. The Customer segment was classified as a niche market with Government as the largest consumer, and the rest was native chicken farmers. The value proportion was to offer vaccinated DOC of native chicken form pure local strain that meets the consumers’ demand. Even though the most effective promotion and sales media was Facebook, PT PQR was unable to increase customer loyalty. The company income resources were sales of DOC, live birds, and fresh-cut native chicken. The main resources were machine, building facilities, and intellectual resources such as ISO management system, cooperation with some experts of BALITNAK and BPATP, and expert staff. The partnership was performed by the acquisition of resources and key activities. Key activities were production activity which relates to transportation from cages-egg reception, egg selection-fumigation-storage in cooling room-hatch-transfer-candling-pull chick. The highest production costs of native chicken DOC were feed and vaccine costs. The improvement programs were increasing production capacity, increasing the number of employees, and cooperating with other native chicken companies.Keywords: business model, business model canvas, business strategic, native chicken, productionAbstrak: Program pemerintah Indonesia tahun 2018-2019 mengenai pembagian DOC ayam kampung dalam rangka penanggulangan kemiskinan, PT PQR ditunjuk sebagai supplier DOC ayam kampung. Penelitian ini bertujuan menganalisis model bisnis PT PQR saat ini dengan bisnis kanvas model serta alternatif perbaikan model bisnisnya Metode penelitian dengan menggunakan Model Bisnis Kanvas. Segmen pelanggan termasuk pasar ceruk, yaitu Pemerintah yang merupakan pelanggan terbesar, sedangkan pelanggan lainnya ialah peternak ayam kampung. Proporsi nilai berupa penawaran galur murni ayam kampung kampung kualitas DOC sesuai keinginan pelanggan, dan DOC sudah divaksin. Saluran terefektif untuk sarana promosi dan penjualan ialah facebook, walaupun demikian PT PQR kurang dapat meningkatkan kesetiaan pelanggan. Sumber pendapatan perusahaan berasal dari penjualan DOC ayam kampung, ayam kampung hidup, dan ayam kampung potong. Sumber daya utama yang dikuasai berupa fasilitas bangunan dan mesin, dan sumber daya intelektual berupa sistem manajemen ISO, kerja sama dengan Balai Penelitian Ternak, dan staf ahli. Kemitraan dilakukan untuk mengakuisisi sumber daya dan aktivitas tertentu. Aktivitas kunci merupakan aktivitas produksi yang terkait dengan transportasi dari kandang-Penerimaan telur-Penyeleksian telur-Fumigasi-Penyimpanan di cooling room-Pengeraman-Transfer-Candling-Pull chick. Biaya yang paling tinggi untuk memproduksi DOC ayam kampung ialah biaya pakan dan biaya vaksin. Program perbaikan berupa penambahan kapasitas produksi, penambahan jumlah karyawan, dan menjalin kerjasama dengan perusahaan ayam kampung lainnya.Kata kunci: ayam kampung, bisnis kanvas model, model bisnis, strategi bisnis, produksi